1998
DOI: 10.1021/la971020q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Pure Layering at the Solid/Liquid Binary Mixture Interface. Silica/Water−2,5-Dimethylpyridine System

Abstract: Experimental evidence is brought for layering transitions at solid (silica) surfaces in contact with liquid mixtures, i.e., first-order transitions whereby the coverage of the surface jumps by an amount equivalent to one extra monolayer of 2,5-dimethylpyridine (2,5-DMP) adsorbed from a liquid mixture with water. These jumps are similar to surface phase changes whose aspects are all shown on the adsorption isotherms:  coexistence of two values of adsorption for the same bulk equilibrium composition, adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…52 The influence of packing on the surface orientation of uncharged pyridinium rings was also recently hypothesized on the basis of observed steplike changes of the adsorption isotherm. 53 For this uncharged molecule, a possible origin in terms of attractions between the aromatic rings was suggested. In our case, a charged molecule, packing may be further guided and locked in place by electrostatic attraction to the surface of opposite charge.…”
Section: Resultsmentioning
confidence: 98%
“…52 The influence of packing on the surface orientation of uncharged pyridinium rings was also recently hypothesized on the basis of observed steplike changes of the adsorption isotherm. 53 For this uncharged molecule, a possible origin in terms of attractions between the aromatic rings was suggested. In our case, a charged molecule, packing may be further guided and locked in place by electrostatic attraction to the surface of opposite charge.…”
Section: Resultsmentioning
confidence: 98%
“…Lutidine is known to adsorb strongly to silica, and 2,5-lutidine and 2,4,6-dimethylpyridine have been shown to adopt a face-on configuration to the silica surface, with bonding occurring between the bridging oxygen in siloxane bonds or deprotonated silanol groups and the aromatic p-system of the pyridine derivative [22,23]. It is reasonable to assume that the same bonding occurs for 2,6-lutidine.…”
Section: Discussionmentioning
confidence: 99%
“…Here we are interested in the small organic molecule 2,6-dimethylpyridine which is quite similar to 2,5-dimethylpyridine and 2,4,6-trimethylpyridine which were studied by Privat et al [22,23]. The fumed silica used in those experiments had <3 OH nm À2 compared to the 4.6 OH nm À2 typical for solution-prepared silica [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 2,5-DMP adsorption on silica from aqueous solutions showed a marked layering effect on adsorption isotherms at different temperatures. 1 This result is quite new at liquid-mixture/solid interfaces whereas it has been known for long in the case of gas adsorption on solids 2 and identified as successive surface phase transitions. For gas-solid systems, a more elaborated phase diagram exhibits gas-liquid-solid transitions [3][4][5] for the lowest surface concentrations.…”
Section: Introductionmentioning
confidence: 84%
“…Considering the multiplicity of phases potentially exhibited by a binary mixture, one may wonder what kind of phases will be seen on surfaces at room temperature. Previous experiments 1,7 showed that, for the water-2,5-DMP-on-silica system, prewetting can be seen as a liquidliquid demixing identical to the bulk phase change close to the one where prewetting occurs whereas layering could be attributed to a kind of liquid-solid demixing identical to the possible bulk phase change that occurs at lower temperature. This process is observed in surface phase…”
Section: Theorymentioning
confidence: 97%